1988
DOI: 10.1111/j.1365-2044.1988.tb06641.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol: clinical strategies for preventing the pain of injection

Abstract: Summary Eight modes of administration of propofol were assessed in order to minimise the pain of injection. An intravenous bolus injection in the antecubital fossa was the only approach that caused no pain. When administered intravenously in the dorsum of the hand the pain score and the number of patients who experienced pain was reduced significantly by mixing the agent with lignocaine when compared with a bolus injection. Slowing the speed of injection caused the greatest discomfort. An indirect biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
269
2
16

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(304 citation statements)
references
References 10 publications
7
269
2
16
Order By: Relevance
“…However, propofol has its own side-effects such as pain on injection [8,9] and greater respiratory depression [10]. Sevoflurane is suitable for quick inhalational induction technique even in high concentrations because of its low blood gas solubility (0.69) [11] and minimal respiratory irritant effect [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, propofol has its own side-effects such as pain on injection [8,9] and greater respiratory depression [10]. Sevoflurane is suitable for quick inhalational induction technique even in high concentrations because of its low blood gas solubility (0.69) [11] and minimal respiratory irritant effect [12].…”
Section: Discussionmentioning
confidence: 99%
“…[2,4,[14][15][16][17] Hovewer, even in patients who received most popular lidocaine treatment, the incidence of pain has been reported as frequent as 32%-48%. [15] Propofol is an excellent anesthetic that belongs to the group of phenols, which can irritate the skin, mucous membrane and venous intima.…”
Section: Discussionmentioning
confidence: 99%
“…These include the addition of lidocaine, cooling or warming the drug, diluting the propofol solution, injection of propofol into a large vein, previous injection of ondansetron, granisetron, metoclopromide, magnesium, thiopental with or without tourniquet. [1][2][3][4][5][6][7] Esmolol is an ultra short acting, cardioselective beta-1 adrenergic receptor antagonist. [8] It is effective in preventing adrenergic responses to several perioperative stimuli, including laryngoscopy, endotracheal intubation with tracheal intubation, intraoperative events and tracheal extubation.…”
Section: Introductionmentioning
confidence: 99%
“…For reduction the injection pain of propofol, the most studied drug was lidocaine administered before and during its injection [13][14][15][16][17][18]. It was stated in many studies that for reducing the injection pain, adding lidocaine to propofol was more effective than applying IV lidocaine before propofol [4,5,7,[10][11][12][13][14][15][16][17][18][19][20]. Kam et al [8] concluded that there was no significant difference between the injection pain caused by propofol MCT/LCT without lidocaine and standard propofol with 10-mg lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Free concentrations of propofol release brandikinin by activating the kinin-kallikrein system with a direct irritation to vessel endothelium (particularly tunica media and intima), thus venous dilatation generates a hyper permeability and this causes pain by providing more contact from propofol to nerve endings [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%